Metabolismo do nitrogênio e carbono em plantas de seringueira submetidas à hipoxia e diferentes fontes de nitrogênio - Carvalho, Pollyanna Aparecida de (2015)
In this study, we aimed at evaluating the physiological changes in rubber tree plants under hypoxia in the presence of NO3- or NH4+. We evaluated the carbohydrate metabolism, antioxidant system and nitrogen (N) assimilation and transport. Two experiments were conducted. In the first, 12 months old plants (RRIM 600) were subjected to nutrient solution N free, with 8 mM N (KNO3) or 8 mM N ((NH4)2SO4) and two oxygen conditions, normoxia and hypoxia. Analyzes were performed at 7, 14 and 21 days after treatments induction. In the second, we evaluated the NO3- or NH4+ interact versus oxygen conditions in six months old plants (GT1). Analyzes were performed at 12, 24, 48 and 72 hours after treatments induction. The results showed that, in the roots, flooding reduced NO3- and N content and the activity of the GS/GOGAT system. In addition, increased NR activity andNH4+ and free amino acids quantities. In the xylem, hypoxic treatment favored NH4+ transport and reduced NO3- transport. The amino acid composition of both root and xylem sap changed in relation to the increase in Gaba alanine from aspartate and glutamate consumption. In the leaves, hypoxic stress reduced NO3- and total amino acids content. The opposite occurred with NH4+ content, GS/GOGAT and GDH activities and serine, glycine and alanine concentrations. In addition, photosynthesis, stomatal conductance, transpiration rate, carbohydrate content and invertase activities decreased in the stressed plants, on the other hand, SOD, CAT, APX activities and H2O2 content increased in both leaves and roots, regardless nitrogen source . We verified that there were changes in nitrogen and carbon metabolisms, as well as in the antioxidant system of rubber trees under hypoxic conditions. We also found that NO3- and NH4+ influenced plant response to hypoxia in different ways. The comparison between the nitrogen sources showed that NO3- metabolism minimized the effects of flooding.